Relationship between Work-Life Balance and Resilience of Early Childhood Teachers - Vitaya-apibalkul, Karantharak; Khayankij, Sasilak; Jiarakul, Nathinee (An Online Journal of Education, 2023)
The purposes of this research were study the relationship between work-life balance and resilience of early childhood teachers. The sample used in the research was 111 early childhood teachers in teacher vocational experience unit school, faculty of Education Yala Rajabhat University, academic year 2022. The research tools were questionnaires. The data was analyzed by frequency distribution, percentage, mean, standard deviation, and the Spearman’s rank correlation coefficient. The results found; early childhood teachers perceived overall work-life balance at a high level (M = 4.28, S.D. = .574) and perceived overall resilience as normal (M = 3.07, S.D. = .295), and Work-life balance had a statistically significant positive correlation with resilience at the .01 level, having a moderate correlation (r = .325).